Diagnosis Of Cholesterol Disease In Adolescence Using Certainty Factor Method - Wardhani, Kusuma; Sihombing, Marto; Syahputra, Siswan (Yayasan Kita Menulis, 2023)
Expert system is a computer program designed to emulate the abilities of an expert in solving problems in a particular field. This system can assist in making a decision and provide a solution based on the data that has been obtained. Delia General Hospital (RSU) is a hospital in Langkat district that provides health services to the community to cure diseases, one of which is cholesterol. Cholesterol is a fatty substance contained in the blood and produced by the body. Cholesterol has an important role in helping to produce hormones and form cells. However, if the level of cholesterol in the blood is too high, it can cause health problems such as atherosclerosis, stroke, and heart disease. Increased cholesterol levels occur in adolescents due to unhealthy lifestyles and consuming foods high in fat. Certainty factor is a method in artificial intelligence that is used to determine whether a fact is certain or uncertain and provides accurate results by calculating the weight of symptoms determined by an expert and can produce answers to uncertain questions.